Assessing changes in genomic divergence following a century of human‐mediated secondary contact among wild and captive‐bred ducks. Issue 3 (8th January 2020) - Lavretsky, Philip; McInerney, Nancy Rotzel; Mohl, Jonathon E.; Brown, Joshua I.; James, Helen F.; McCracken, Kevin G.; Fleischer, Robert C.
Abstract: Along with manipulating habitat, the direct release of domesticated individuals into the wild is a practice used worldwide to augment wildlife populations. We test between possible outcomes of human‐mediated secondary contact using genomic techniques at both historical and contemporary timescales for two iconic duck species. First, we sequence several thousand ddRAD‐seq loci for contemporary mallards ( Anas platyrhynchos ) throughout North America and two domestic mallard types (i.e., known game‐farm mallards and feral Khaki Campbell's). We show that North American mallards may well be becoming a hybrid swarm due to interbreeding with domesticated game‐farm mallards released for hunting. Next, to attain a historical perspective, we applied a bait‐capture array targeting thousands of loci in century‐old (1842–1915) and contemporary (2009–2010) mallard and American black duck ( Anas rubripes ) specimens. We conclude that American black ducks and mallards have always been closely related, with a divergence time of ~600, 000 years before present, and likely evolved through prolonged isolation followed by limited bouts of gene flow (i.e., secondary contact). They continue to maintain genetic separation, a finding that overturns decades of prior research and speculation suggesting the genetic extinction of the American black duck due to contemporary interbreeding with mallards. Thus, despite having high rates of hybridization, actual gene flow is limited between mallards and American black ducks. Conversely, our historical and contemporary data confirm that the intensive stocking of game‐farm mallards during the last ~100 years has fundamentally changed the genetic integrity of North America's wild mallard population, especially in the east. It thus becomes of great interest to ask whether the iconic North American mallard is declining in the wild due to introgression of maladaptive traits from domesticated forms. Moreover, we hypothesize that differential gene flow from domestic game‐farm mallards into the wild mallard population may explain the overall temporal increase in differentiation between wild black ducks and mallards, as well as the uncoupling of genetic diversity and effective population size estimates across time in our results. Finally, our findings highlight how genomic methods can recover complex population histories by capturing DNA preserved in traditional museum specimens.